Perancangan Vest Dengan Teknik Patchwork Menggunakan Kain Perca Motif Batik Tanah Liek: Perancangan Vest dengan Teknik Patchwork Menggunakan Kain Perca Motif Batik Tanah Liek - Muliandra, Aristi; Sesnawati, Yeni; Wesnina, Wesnina (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
This research aims to determine the assessment of vest products using patchwork techniques using Tanah Liek batik patterns. This research uses an experimental research method of the Pre-Experimental Design type with a one-shot case study design. The data obtained used a mixed questionnaire research instrument, and the scale used was the Rating Scale with a value range between 1-5 (Very Poor – Very Good). The results of the research assessment of vest products using patchwork techniques with Tanah Liek batik pattern based on the product quality aspect were in the good category, then the assessment based on design elements also got the good category, and finally the assessment based on the design principle aspect was also in the good category so that It can be concluded that in the three assessment aspects used to evaluate vest products with patchwork techniques with Tanah Liek batik patterns, they are all in the good category. Vest design with patchwork technique with Tanah Liek batik pattern, design 1 gets the highest score which is in the very good category, while the design with the lowest score is obtained by design 3 which is in the good category.